DIGITAL TECHNOLOGIES IN MASTER'S TRAINING FROM CREATIVE INDUSTRIES - Gorodianska, Larysa; Zasenko, Serhii (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The directions of introducing digital technologies into the educational process of creative industries master’s are substantiated. The priority ways of improving profile academic disciplines of master’s are determined, the main of which are: distance and blended learning; Virtual Reality; Augmented Reality. Based on the findings, the organization of the educational process must take into account digital technologies by ensuring that teachers and master's students of higher educational institutions possess adequate digital competencies, which will ensure high quality training of the fine arts students.